PROSES MANUFAKTUR BILAH TAPERLESS DENGAN AIRFOIL NACA 4412 BERBAHAN RESIN DAN SERAT RAMI - Fikri Hanif Albari (2021)
The use of electricity generation using renewable energy is growing very quickly, one of which is Wind Power Plants. One of the main components is the blade, the blade functions as a means of converting kinetic energy into mechanical energy to turn a generator. Composite material is one of the materials for making blades, and one of the main ingredients is fiber. The hemp fiber that the author uses is one of the variations of fiber for composite slats. The manufacturing process consists of 4x2 layers, with the constituent materials, namely, resin, hemp fiber, aerosil, WR200 and catalyst, using the Hand lay-up method. With the test results obtained such as stress 8,667 mpa, strain 43,667% and elastic modulus of 210,57 mpa. Hemp fiber can be a variation of fiber as a composite material for wind turbine blades.